Pengaruh Peran Guru dalam Mengembangkan Komunikasi Efektif pada Anak Usia Dini 4-5 Tahun - Nurul Aini MM Sodik; Melia Frilia Pakaya; Fitriyawati Ladiku; Nurwila Ye’ete; Nabila Nggai (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2026)
Effective communication is an important element in the early childhood learning process because it plays a significant role in children’s social, emotional, and cognitive development. This study aims to determine the influence of teachers’ roles in developing effective communication among early childhood children aged 4–5 years at TK Damhil, Kota Selatan, Gorontalo Province. The research used a quantitative method with a descriptive research design. The research subjects consisted of 5 children aged 4–5 years selected through purposive sampling techniques. Data collection techniques were carried out through direct observation of children’s communication activities during the learning process. The results showed that the teacher’s role is very important in building effective communication through the use of simple language, responsive attitudes, active listening skills, and the use of verbal and nonverbal communication that is appropriate to children’s developmental characteristics. The implementation of effective communication was proven to improve children’s self-confidence, social interaction skills, and readiness to face formal education. Therefore, effective communication applied by teachers provides a positive contribution to optimizing early childhood development.